2006
DOI: 10.1590/s0103-84782006000100004
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento de grãos de soja em função de diferentes sistemas de manejo de solo e de rotação de culturas

Abstract: O objetivo do presente trabalho foi avaliar sistemas de manejo de solo e de rotação de culturas sobre o rendimento de grãos e componentes do rendimento de soja durante seis anos. Foram comparados quatro sistemas de manejo de solo - 1) plantio direto, 2) cultivo mínimo, no inverno e semeadura direta, no verão, 3) preparo convencional de solo com arado de discos, no inverno e semeadura direta, no verão e 4) preparo convencional de solo com arado de aivecas, no inverno e semeadura direta, no verão - e três sistem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
5
0
9
Order By: Relevance
“…Still in the previous study, with this same experiment, from 1997/1998 to 2002/2003, the soybean grown after wheat (2,866 kg ha -1 ), in the system II, was superior to that grown after white oat (2,799 kg ha -1 ) and after wheat (2,804 kg ha -1 ), in the system III, and after wheat (2,636 kg ha -1 ), in the system I (Santos et al, 2006). The lowest values of grain yield, grain weight per soybean plant and 1,000-grain weight was observed in monoculture soybean.…”
Section: Resultsmentioning
confidence: 81%
“…Still in the previous study, with this same experiment, from 1997/1998 to 2002/2003, the soybean grown after wheat (2,866 kg ha -1 ), in the system II, was superior to that grown after white oat (2,799 kg ha -1 ) and after wheat (2,804 kg ha -1 ), in the system III, and after wheat (2,636 kg ha -1 ), in the system I (Santos et al, 2006). The lowest values of grain yield, grain weight per soybean plant and 1,000-grain weight was observed in monoculture soybean.…”
Section: Resultsmentioning
confidence: 81%
“…This demonstrates the importance of notillage in increasing soybean tolerance to hydric stresses (FRANCHINI et al, 2009), increasing the bond number and strength of soil aggregates by age-hardening phenomena (MORAES et al, 2017), improving soil aggregation and its structure that allows greater storage of available water (SILVA et al, 2014), upward flow of water from the deeper layers to the more superficial layers of water (MORAES et al, 2016) and increased rooting depth (MORAES, 2017). Santos et al (2006) observed that, independently of crop rotation systems, soybean cultivated under no-tillage showed higher grain yields, a greater mass of 1,000 grains, with higher plant height than soybean cultivated under conventional tillage system, with disk plow or turning plow.…”
Section: Resultsmentioning
confidence: 96%
“…These authors observed a 17% increase in the average yield of soybean, under rotation system with maize, in relation to that observed in the succession with wheat. Santos et al (2006) reported that the higher grain yields in crop rotation systems relative to the wheat / soybean succession model were related, in part, to the final population of plants, the grain mass per plant, the mass of thousand grains and the height of soybean plants.…”
Section: Resultsmentioning
confidence: 99%
“…foi determinada por meio da percentagem de plantas que apresentaram o sintoma no total de 20 plantas por parcela, no estádio fenológico R6 da soja, tendose observado o sintoma na área foliar, conhecido como folha carijó, que é caracterizado por manchas cloróticas e necróticas internervais, com coloração verde normal, na região das nervuras, e com coloração castanho-claro a castanho-avermelhado escuro, na raiz (Almeida et al, 2005 (Kluthcouski et al, 2000). Já Santos et al (2006b) verificaram que, independentemente de rotação, a soja cultivada sob plantio direto e sob cultivo mínimo apresenta maior produtividade, maior massa de mil grãos e maior altura de plantas, em comparação à soja cultivada sob preparo convencional de solo. Tabela 1.…”
Section: Methodsunclassified